Insights into the complex relationship between triglyceride glucose-waist height ratio index, mean arterial pressure, and cardiovascular disease: a nationwide prospective cohort study - Jie Xu; Dihui Cai; Yuheng Jiao; Yingying Liao; Yinyin Shen; Yunli Shen; Wei Han (Cardiovascular Diabetology)
Abstract Background Both the triglyceride glucose-waist height ratio (TyG-WHtR) index and elevated arterial blood pressure are risk factors for cardiovascular disease (CVD). However, it is uncertain whether the TyG-WHtR index can increase the risk of CVD by influencing arterial blood pressure, and the extent to which the TyG-WHtR index may mediate the association between arterial blood pressure and CVD. The purpose of this study is to evaluate complex association of the TyG-WHtR index and mean arterial pressure (MAP) with CVD. Methods All data in this study were obtained from the China Health and Retirement Longitudinal Study (CHARLS) free of CVD at baseline. CVD was defined as self-reporting heart disease and stroke. Cox proportional hazards model and restricted cubic spline (RCS) were used to analyze the association of the TyG-WHtR index and MAP with the risk of CVD. Time-dependent receiver operating characteristic (ROC) analysis was used to assess the predictive performance of TyG-WHtR, MAP for CVD. Four-way decomposition method explored the mediating effects of the TyG-WHtR index and MAP in CVD. Results A total of 7976 participants were included in this study. The mean age of the participants was 58.68 ± 9.60 years, and 4263 (53.45%) were females. During a maximum follow-up of 7.0 years, 1326 (16.62%) people developed CVD. Both the TyG-WHtR index and MAP were signifcantly associated with CVD. The RCS regression analyses demonstrated a positive linear association of the TyG-WHtR index and MAP with the incidence of CVD. Compared with participants with TyG-WHtR < median and MAP < median, those with TyG-WHtR ≥ median and MAP ≥ median had the highest risk of CVD (HR 1.961; 95%CI 1.660–2.317). The combination of TyG-WHtR and MAP demonstrated incremental predictive utility over either biomarker alone, as evidenced by improvements in integrated discrimination improvement (IDI) and net reclassification improvement (NRI). While absolute predictive performance remained moderate. Increased MAP signifcantly mediated 52.43% of the associations between TyG-WHtR index and CVD, and increased TyG-WHtR index signifcantly mediated 83.40% of the associations between MAP and CVD. Conclusion The combination of a higher TyG-WHtR index and a higher MAP was associated with the highest risk of CVD. The combined model of the TyG-WHtR index and MAP showed improved predictive ability, as indicated by IDI and NRI, although its overall predictive performance was still moderate. The MAP could partially mediate the association between TyG-WHtR index and CVD, as well as TyG-WHtR index could also partially mediate the association between MAP and CVD. These findings suggested that the combination of TyG-WHtR index and MAP helps identify populations at early risk of CVD and improve risk stratifcation. Graphical abstract